Platet Rich Plasma or Hyperbaric Oxygen Therapy as callus accellerator in aseptic tibial non union. Evaluate of outcomes. - Rollo, Giuseppe; Bonura, Enrico Maria; Falzarano, Gabriele; Bisaccia, Michele; Ribes Iborra, Julio; Grubor, Predrag; Filipponi, Marco; Pichierri, Paolo; Hitov, Philip; Leonetti, Danilo; Russi, Valentina; Daghino, Walter; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The incidence of long bone non-unions has been estimated to range between 5-10%. Nonunion of fracture is a delayed complication of fracture. A large bone resection, associated with Ilizarov's osteo-distraction technique, is commonly used in these cases. The war experience was very important for dealing with these injuries. The purpose of this study is to report whether the use of Platelet Rich of Plasma(PRP) or Hyperbric Oxygen Therapy(HOT) as an adjuvant to the osteogenic distraction of Ilizarov with respect to the classical method has advantages.Methods: From 183 tibial non union, we enrolled 50 patients suffering by Type B according ASAMI non union classification.  We divided the patients into two groups. The first group was a retrospective group of patient treated by Ilizarov Tecnique plus PRP. Instead the second group, patients were treated by Ilizarov Tecnique associated with  HOT. The chosen criteria to evaluate the two groups during the clinical and radiological follow-up were: the complication after the surgery in the two groups; the duration of surgery; the objective quality Bone results and functional results were evaluated according to ASAMI classification while the subjective quality of  life correlated with Ilizarov frame function by the Short Form 12 Health Survey (SF-12); The correlation between bone regenerate/bone healing and X-rays. The evaluation endpoint was set at 12 months from the remotion of Ilizarov’s frame for both groups.Results: In comparing the complications  of the two populations, there were a significant statistically difference(p